Fibrinolysis Shutdown and Thrombosis in a COVID-19 ICU. Issue 3 (March 2021) - Creel-Bulos, Christina; Auld, Sara C.; Caridi-Scheible, Mark; Barker, Nicholas A.; Friend, Sarah; Gaddh, Manila; Kempton, Christine L.; Maier, Cheryl L.; Nahab, Fadi; Sniecinski, Roman
Abstract : ABSTRACT: The coronavirus disease (COVID-19) pandemic has threatened millions of lives worldwide with severe systemic inflammation, organ dysfunction, and thromboembolic disease. Within our institution, many critically ill COVID-19-positive patients suffered major thrombotic events, prompting our clinicians to evaluate hypercoagulability outside of traditional coagulation testing. We determined the prevalence of fibrinolysis shutdown via rotational thromboelastometry (ROTEM, Instrumentation Laboratories, Bedford, Mass) in patients admitted to the intensive care unit over a period of 3 weeks. In 25 patients who had a ROTEM test, we found that 11 (44%) met criteria for fibrinolysis shutdown. Eight of 9 (73%) of the VTE patients met criteria for fibrinolysis shutdown. Given the high rate of fibrinolysis shutdown in these patients, our data support using viscoelastic testing to evaluate for the presence of impaired fibrinolysis. This may help identify patient subsets who might benefit from the administration of fibrinolytics.